Circulating Interleukin-17A is associated with executive function in middle aged adults with and without type 2 diabetes - Laura Morrison; Adam H. Dyer; Helena Dolphin; Isabella Batten; Conor Reddy; Matthew Widdowson; Conor P. Woods; James Gibney; Nollaig M. Bourke; Sean P. Kennelly (Brain, Behavior, & Immunity - Health, 2024)
Midlife cardiovascular risk factors such as Type 2 Diabetes (T2DM) and obesity are associated with the later development of cognitive impairment and dementia. Systemic inflammation is postulated as a crucial mechanism, yet there are few studies examining this at the earliest stages prior to overt cognitive impairment. To assess this, we recruited a cohort of middle-aged cognitively-unimpaired individuals with and without uncomplicated T2DM. Comprehensive neuropsychological assessment was performed at baseline and at 4-year follow-up. Ten serum chemokines and cytokines (Eotaxin, MCP-1, MIP-1β, CXCL10, IL-6, IL-10, IL12p70, IL-17A, IFN-γ and TNF-α) were measured at both baseline and follow-up using high-sensitivity assays. Overall, 136 participants were recruited including 90 with uncomplicated midlife T2DM (age 52.6 ± 8.3; 47% female) and 46 without (age 52.9 ± 8.03; 61% female). Cognitive trajectories were stable over time and did not differ with T2DM. Yet on cross-sectional analyses at both baseline and follow-up, greater circulating IL-17A was consistently associated with poorer performance on tests of executive function/attention (β: 0.21; −0.40, −0.02, p = 0.03 at baseline; β: 0.26; −0.46, −0.05, p = 0.02 at follow-up). Associations persisted on covariate adjustment and did not differ by T2DM status. In summary, we provide evidence that greater circulating IL-17A levels were associated with poorer executive function in midlife, independent of T2DM. Long-term follow-up of this and other cohorts will further elucidate the earliest stages in the relationship between systemic inflammation and cognitive decline to provide further mechanistic insights and potentially identify those at greatest risk for later cognitive decline.